Pengaruh Mucuna bracteata dan Kemiringan Lahan Terhadap Keragaman Makrofauna Tanah serta Pertumbuhan Akar Tanaman Kelapa Sawit Belum Menghasilkan - Tamrin, Muhammad; Wawan, Wawan; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aimresearchof determine the influence of M. bracteata and the slope of land to the diversity of soil macrofauna and root growth of oil palmsimmature. This research was conducted in PTPN V Unit LubukDalam, Siak and analysis of soil macrofauna in the Soil Laboratory Faculty of Agriculture, University of Riau. This research has been carried out from January to April 2016. The study was conducted using Split Plot Design. The level of the slope (K) as the main plot consists of: K0 = 0-3%,K1 =>3-8%, K2 = >8-15%. Employing Mucunabracteata (M) as the subplot consisting of: M0 = land clearning, M1 = land that is overgrown. The parameters measured were the number of population density, relative density, diversity index (H’) soil macrofauna, root dry weight, root volume and root occupy. The research showed: (1) land overgrown palm M. bracteata has a population density number, relative density and the diversity of the soil macrofauna higher and better root growth compared with that land clearning; and (2) The higher the slope (%) resulting in a population density, relative density and the diversity of soil macrofauna are getting lower and root growth decreases. Keywords: Mucuna bracteata, land slope and macrofauna